2016
DOI: 10.3390/en9090714
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Depressurization Process of a Natural Gas Hydrate Reservoir: An Attempt at Optimization of Field Operational Factors with Multiple Wells in a Real 3D Geological Model

Abstract: Natural gas hydrates, crystalline solids whose gas molecules are so compressed that they are denser than a typical fluid hydrocarbon, have extensive applications in the areas of climate change and the energy crisis. The hydrate deposit located in the Shenhu Area on the continental slope of the South China Sea is regarded as the most promising target for gas hydrate exploration in China. Samples taken at drilling site SH2 have indicated a high abundance of methane hydrate reserves in clay sediments. In the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This study found that solving the coupled problem separately often led to better solutions than the simultaneous solution, potentially because the smaller solution space of the decoupled problem makes finding good solutions easier. Similar results have also been found for nonconventional wells [126,127]. Drouven and Grossmann [128] have applied Generalized Disjunctive Programming (GDP) coupled with a tailored solution method utilizing gradient based optimizers to well location optimization of shale gas wells combined with surface gathering system design and operational considerations.…”
Section: Coupled Well Placement and Well Control Optimizationmentioning
confidence: 52%
“…This study found that solving the coupled problem separately often led to better solutions than the simultaneous solution, potentially because the smaller solution space of the decoupled problem makes finding good solutions easier. Similar results have also been found for nonconventional wells [126,127]. Drouven and Grossmann [128] have applied Generalized Disjunctive Programming (GDP) coupled with a tailored solution method utilizing gradient based optimizers to well location optimization of shale gas wells combined with surface gathering system design and operational considerations.…”
Section: Coupled Well Placement and Well Control Optimizationmentioning
confidence: 52%
“…Kim et al [26] provided a comprehensive estimation for model parameters and properties based on vast data from field seismic surveys in Ulleung basin and laboratory experimental results. Numerical studies on the efficiency and productivity of gas hydrate production have been carried out continuously, while stability analysis for the hydrate-bearing sediments or wellbore has not been much considered, although stability analysis is essential to field production [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrate-forming gas molecules (e.g., CH 4 , C 2 H 6 and CO 2 ) are usually small and light, and the hydrate is found to have three types of structures in nature (i.e., Type I, II and H) [2,3]. Formation and dissociation processes of NGH can be simply expressed by the reversible reaction equation below [4][5][6]: (1) In Equation 1, n H is the hydration number, and ∆H en is the enthalpy of hydrate formation or dissociation. NGH is a high-density energy source.…”
Section: Introductionmentioning
confidence: 99%